Collective bargaining's contribution to employment skills and transitions: lessons from the nordic countries. (3rd July 2021) - Scott, Andrew
ABSTRACT: Major shifts in employment patterns – across sectors, occupations and regions – are a constant feature of modern labour markets. These transitions can occur in more or less humane and efficient ways, depending on whether active policies are leveraged to support workers, employers and industries to adapt to change and take advantage of new opportunities. The imperative to better manage employment transitions is all the more pressing given the necessary shift towards a carbon-neutral, sustainable economy. The very high collective bargaining coverage in Nordic countries contributes to their active labour market policy, proper regulation of employment standards, high-quality investments in skills and innovation, integrated vocational planning, and comprehensive social solidarity. This article will identify how strong collective bargaining in Nordic countries enhances workforce skills, adaptability and innovation, and the lessons from this to improve the more laissez-faire transitions currently occurring in liberal market economies such as Australia.